COMPARISON OF ORAL DAPSONE WITH INTRAMUSCULAR MEGLUMINE ANTIMONIATE IN CUTANEOUS LEISHMANIASIS - Najia Ahmed,; Sadia Malik,; Tahir, Moizza; Atiya Rahman,; Ifrah Fayyaz,; Naeem Raza,; Nadia Iftikhar, (Journal of Ayub Medical College Abbottabad, 2022)
Background: Many drugs are effective are used as second line treatment for cutaneous leishmaniasis. Dapsone therapy is tolerated well and cost effective. The aim of present study is to determine the efficacy of oral dapsone in comparison with intramuscular meglumine antimoniate in patients with cutaneous leishmaniasis and thus find out an effective second line treatment agent. Methods: This randomized controlled trial was carried out at dermatology department, of tertiary care centre Rawalpindi, Pakistan from November 2017 to June 2018. Hundred biopsy proven patients of cutaneous leishmaniasis completed the study with 50 patients in two group. Group A received intramuscular meglumine antimoniate (15 mg/kg/day). Group B received oral dapsone2.5 mg /kg/body weight /day (200 mg per day). Efficacy of therapeutic response was noted at the end of treatment. Data was analyzed with statistical analysis program (IBM-SPSS V22). Chi-square test was applied to compare efficacy, p value of ‰¤0.05 was significant. Stratification of data with respect to age, gender, duration of disease, number of lesions and weight was done to see their effect on treatment efficacy. Post stratification chi-square test for both groups was applied (p‰¤0.05 considered significant). Results: A total of 100 participants took part in the study. Duration of treatment (p-value <0.001) and the efficacy of the drugs (p-value=0.020) were significant. Meglumine antimoniate therapy group displayed a comparatively fast-paced recovery in (21-40 days) whereas Dapsone group showed better recovery in (41-60 days) in their lesions. Conclusion: Dapsone is an effective treatment for cutaneous Leishmaniasis. Results: A total of 100 participants took part in the study. Duration of treatment (p-value <0.001) and the efficacy of the drugs (p-value=0.020)were significant. Meglumine antimoniate therapy group displayed a comparatively fast-paced recovery in (21-40 days) whereas Dapsone group showed better recovery in (41-60days) in their lesions. Conclusion: Dapsone is an effective treatment for cutaneous Leishmaniasis